Study of head and neck squamous cell carcinoma transcriptome after proton therapy - E. D. Jumaniyazova; P. A. Vishnyakova; M. V. Chirkova; E. A. Karpulevich; I. Z. Eremina; K. B. Gordon; A. D. Kaprin; T. H. Fatkhudinov (Бюллетень сибирской медицины, 2024)
Aim. To evaluate changes in the transcriptome of head and neck squamous cell carcinoma (HNSCC) tissue cells in patients after proton therapy.Materials and methods. Biopsy material obtained from 3 HNSCC patients before and after proton therapy at a total dose of 10 isoGy was homogenized, purified, and concentrated. Then total RNA was isolated with further purification and concentration with the RNA Clean & Concentrator kit (Zymo Research). Library quantitation was assessed using the Qubit 2.0 instrument (Invitrogen, Life Technologies). After isolation of 1 μg total RNA for sequencing, libraries were prepared on the Illumina platform using the TruSeq RNA Sample Prep Kit v2 with a 10-cycle enrichment step according to the manufacturer’s recommendations. The quality of RNA and the resulting libraries was checked using the Agilent 2100 Bioanalyzer system (Agilent Tec. Inc., USA). The RIN parameter for RNA was at least 7. The library concentration was assessed by real-time PCR on the CFX96 Touch Real-Time PCR Detection System (Bio-Rad, USA). Final libraries were pooled in equimolar ratios before sequencing on the Illumina HiSeq 2500 platform using 50 base-pair paired-end reads. The Q20 parameter for all samples was > 97%, and the number of reads averaged 60.2 million per sample. Raw reads were processed using the RTA 1.17.21.3 and Casava 1.8.2 (Illumina). The enrichment analysis was performed using the PANTHER 17.0 software.Results. The transcriptome analysis of HNSCC after proton radiation therapy (5 x 2 isoGy) at a total dose of 10 isoGy revealed 1,414 significantly differentially expressed genes. The 10 most and least expressed genes and their associated signaling pathways were identified. A number of signaling pathways associated with the underexpressed genes were detected in HNSCC after proton therapy, such as: STAT5; PD-1 signaling pathway; marked MET-mediated activation of PTK2 signaling pathway, PDGF signaling; CD22-mediated regulation of BCR; and FCERI-mediated MAPK activation. In addition to the above signaling pathways, activation of collagen degradation, FCGR3A-mediated phagocytosis, and FCGR3A-mediated interleukin (IL)-10 synthesis are of interest. In the enrichment analysis among highly expressed genes, keratinization and biological oxidation processes were activated in HNSCC tissues after proton therapy.Conclusion. Proton therapy in HNSCC leads to overexpression of genes involved in the regulation of keratinization and biological oxidation processes as well as to underexpression of genes associated with suppression of signaling pathways: STAT5, PD-1, MET-mediated activation of PTK2 signaling pathway, PDGF signaling; CD22-mediated regulation of BCR; FCERI-mediated MAPK activation, collagen degradation, FCGR3A-mediated phagocytosis activation, and FCGR3A-mediated IL-10 synthesis. All signaling pathways of underexpressed genes function in HNSCC cells if there is no negative influence on the tumor from outside (irradiation or delivery of antitumor drugs). The predominance of suppressed signaling pathways over activated ones most likely indicates a decrease in the functional potential of cells after proton therapy. The dose-dependence of PT effects necessitates further study of changes in cellular and molecular-genetic signatures of HNSCC after proton irradiation with different doses.